Taxonomy of Diamesa steinboecki group (Diptera: Chironomidae: Diamesinae), with description and DNA barcoding of known species. II. Subgroups davisi, leona and loeffleri - Makarchenko, Eugenyi A.; Semenchenko, Alexander A.; Palatov, Dmitry M. (Zootaxa, 2022)
Illustrated redescription of the adult males Diamesa alpina Tokunaga from the Russian Far East and North America, D. amplexivirilia Hansen from Arctic and the Russian Far East, D. saetheri Willassen from Chukotka Region and Kolyma River basin, D. lupus Willassen from Alaska, D. serratosioi Willassen from Norway and Russian Far East, D. leoniella Hansen from Alaska, D. leona Roback from Eurasia, D. japonica Tokunaga from Japan and Russian Far East, D. khumbugelida Saether et Willassen and D. loeffleri Reiss from Himalayas are provided. Morphological data and DNA sequences of the mitochondrial cytochrome c oxidase subunit I gene (COI) were used to delimit of seven species from subgroups davisi (D. alpina, D. amplexivirilia, D. serratosioi), leona (D. japonica, D. leona) and loeffleri (D. khumbugelida, D. loeffleri). Taxonomic remarks with data on geographical distribution of the investigated species are given.